2007
DOI: 10.1016/j.jasms.2007.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed large volume injection gas chromatography coupled with electron-capture negative ionization quadrupole mass spectrometry for simultaneous determination of typical halogenated persistent organic pollutants

Abstract: A pulsed large-volume injection gas chromatography coupled with electron-capture negative ionization quadrupole mass spectrometry (pLVI-GC/ECNI-qMS) was developed for the simultaneous determination of typical halogenated persistent organic pollutants (H-POPs). By monitoring the characteristic ions of large mass-to-charge ratio (m/z) for each of the H-POPs rather than the chlorine and/or bromine ions, this method avoided the possible interferences arising from the H-POPs themselves and from complex matrices enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 34 publications
(30 reference statements)
2
11
0
Order By: Relevance
“…The value in this study was one order of magnitude lower than those obtained by others using bench top GC-EI-Sector-MS [14], LC-LIT-MS [18] and LC-triple quadrupole-MS [20], and were close to the levels obtained using GC-ECNI-MS [15,28] and GC-ICP-MS [19]. Although there is no information on IDL for GC-EI-Sector-MS, it was reported that its sensitivity is the same as that of GC-ECNI-MS [15,28] and GC-ICP-MS [19]. Although the sensitivity of this method was 10 times lower than that of GC-ECNI-MS [16], this method was more selective.…”
Section: Sensitivity and Reliability Of The Methodssupporting
confidence: 78%
“…The value in this study was one order of magnitude lower than those obtained by others using bench top GC-EI-Sector-MS [14], LC-LIT-MS [18] and LC-triple quadrupole-MS [20], and were close to the levels obtained using GC-ECNI-MS [15,28] and GC-ICP-MS [19]. Although there is no information on IDL for GC-EI-Sector-MS, it was reported that its sensitivity is the same as that of GC-ECNI-MS [15,28] and GC-ICP-MS [19]. Although the sensitivity of this method was 10 times lower than that of GC-ECNI-MS [16], this method was more selective.…”
Section: Sensitivity and Reliability Of The Methodssupporting
confidence: 78%
“…Hence, we propose that the positive results primarily resulted from reduced diffusion effects owing to the shorter retention time. It should be noted that the GC/ECNI-MS sensitivity of BDE-209 can be improved on certain instruments by increasing the ion source temperature [37]. In this present case, we observed an improvement by $20% when the ion source temperature was increased from 150 C to 300 C. This effect adds to the effect obtained with our high flow method.…”
Section: Gc/ecni-ms Measurements On 30 M Vs 15 M Columnssupporting
confidence: 63%
“…One had to increase the sample volume, for example, using a pulsed large-volume injection technique, to see the structure-informative fragment ions of PBDEs during a GC/ECNI-qMS. 31 In the case of OH- (Table S1, Supporting Information) can be used for identification.…”
Section: ■ Results and Discussionmentioning
confidence: 99%